Sistem Pakar Identifikasi Penyakit Jamur Kulit Pada Manusia Menggunakan Metode Certainty Factor - Rahman, M. Afif Auliya; Jusak, Dr.; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Indonesia is a tropical country with high levels of humidity . High humidity levels can make a flourish of mushrooms , one of which is a fungal disease of the skin. many people assume that the skin fungal disease if left unchecked it can heal itself . it is so wrong , skin fungal diseases if not faster handling of it will have a negative effect on human health it . one of the adverse effects will occur in humans as a permanent hair loss or hearing loss . the existence of such problems is then made of skin fungal disease expert system uses certainty factor method . in order to help people who suffer from fungal diseases of the skin. after the system is created by the acquisition of knowledge from experts , to replace the expert and has been tested with a black box method can result out of 100 % . so that the system is fit for use by people suffering from fungal diseases of the skin.